Processing Effect On Phytochemical Content Of Elaeagnus Latifolia And Hippophae Salicifolia Of Sikkim Himalayas - N. D. Sherpa ,K. D. Bhutia (International Journal of Advanced Science and Technology, 2020)
The purpose of the research study was to evaluate the effect of processing on the phytochemical content of two wild fruits of Sikkim Himalayas viz., ’Elaeagnus latifolia and Hippophae salicifolia’. The samples of both the fresh and processed products were estimated. Processed products prepared were Elaeagnus latifolia chutney, ketchup and Hippophae salicifolia juice and jelly. It was observed that the thermal processing of fruits led to statistical significant alterations for phytochemical parameters like total antioxidant, ascorbic acid, total phenol, total flavonoids, total anthocyanin and total carotenoids. The practical implications of this work are that the derived knowledge could be very useful to optimize processing technology which will improve the product quality, consumer acceptability, and marketability in future, further as the consumption of the polyphenolics contained in these wild fruit products will provide benefits for human health as these compounds have probability to reduce the diseases like cancer and cardiovascular diseases.